2021
DOI: 10.1155/2021/6637990
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant Effect of Urginea maritima on Tracheal Smooth Muscle Mediated by the Effect on Beta-2 Adrenergic, Muscarinic Receptors and Calcium and Potassium Channels

Abstract: Urginea maritima (U. maritima) showed anti-inflammatory, antioxidant, antibacterial, diuretic, vasodilatation, and wound-healing effects on fungal infections, cardiac disorders, digestive disorders, rheumatoid disease, and respiratory disorders such as bronchitis, bronchial nosocomial infections, and severe cough. To examine the bronchodilatory effect of U. maritima, the relaxant effect of its extract on rat tracheal smooth muscle (TSM) and its possible mechanism was examined in this study. Male Wistar rats’ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For example, traditionally, Urginea maritima (D. maritima) has been utilized for the treatment of cardiac disorders and fungal infections and as a diuretic agent. Hence, Kazemi Rad and colleagues [61] investigated the relaxation effect of U. maritima on rat tracheal smooth muscles. It was suggested that the incubated tissues compressing U. maritima extract showed significantly higher relaxant outcomes compared to the nonincubated tissues.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, traditionally, Urginea maritima (D. maritima) has been utilized for the treatment of cardiac disorders and fungal infections and as a diuretic agent. Hence, Kazemi Rad and colleagues [61] investigated the relaxation effect of U. maritima on rat tracheal smooth muscles. It was suggested that the incubated tissues compressing U. maritima extract showed significantly higher relaxant outcomes compared to the nonincubated tissues.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…It was suggested that the incubated tissues compressing U. maritima extract showed significantly higher relaxant outcomes compared to the nonincubated tissues. The bronchodilatory effect of the plant extract promotes the beta-2 adrenoceptor and prevents the muscarinic receptor, potassium opening and calcium channels [61]. The anti-inflammatory activity of D. nagarjunae extracts from the leaves and bulbs of the plant using in vitro protein denaturation techniques was investigated further.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%